EVALUATING VALUE: A COMPARATIVE DISCOURSE ANALYSIS OF ADJECTIVAL WORDS IN HIGH-END AND BUDGET SMARTPHONE REVIEWS - Anisa, Nurul; Zaidi, Ahmad; Asprillia, Anandya (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study investigates how reviewers linguistically construct evaluations of high-end and budget smartphones through adjective usage in YouTube video reviews. Using a mixed-methods approach, the research analyzes English captions from ten review videos and processes them with AntConc to identify frequency patterns and discourse functions. The findings show clear lexical distinctions between the two categories. High-end smartphone reviews favor adjectives such as new, best, and better, emphasizing innovation, premium identity, and advanced features, including emerging AI-driven functions. In contrast, budget smartphone reviews rely heavily on adjectives like good, same, and little, framing these devices as practical, affordable, and often built upon recycled or minimally improved components. The analysis demonstrates how evaluative language shapes consumer perceptions by positioning flagship models as technologically progressive, while presenting budget devices as sufficient within financial constraints. The discussion connects these findings to existing literature on product discourse, innovation framing, and brand image formation. Overall, the study highlights how linguistic choices in reviews influence consumer expectations, particularly regarding AI advancements in high-end smartphones and camera performance across market tiers.